Risk factors for failure of the 36 mm metal-on-metal Pinnacle total hip arthroplasty system: a retrospective single-centre cohort study. (May 2017) - Matharu, G. S.; Nandra, R. S.; Berryman, F.; Judge, A.; Pynsent, P. B.; Dunlop, D. J.
Abstract : Aims: To determine ten-year failure rates following 36 mm metal-on-metal (MoM) Pinnacle total hip arthroplasty (THA), and identify predictors of failure. Patients and Methods: We retrospectively assessed a single-centre cohort of 569 primary 36 mm MoM Pinnacle THAs (all Corail stems) followed up since 2012 according to Medicines and Healthcare Products Regulation Agency recommendations. All-cause failure rates (all-cause revision, and non-revised cross-sectional imaging failures) were calculated, with predictors for failure identified using multivariable Cox regression. Results: Failure occurred in 97 hips (17.0%). The ten-year cumulative failure rate was 27.1% (95% confidence interval (CI) 21.6 to 33.7). Primary implantation from 2006 onwards (hazard ratio (HR) 4.30; 95% CI 1.82 to 10.1; p = 0.001) and bilateral MoM hip arthroplasty (HR 1.59; 95% CI 1.03 to 2.46; p = 0.037) predicted failure. The effect of implantation year on failure varied over time. From four years onwards following surgery, hips implanted since 2006 had significantly higher failure rates (eight years 28.3%; 95% CI 23.1 to 34.5) compared with hips implanted before 2006 (eight years 6.3%; 95% CI 2.4 to 15.8) (HR 15.2; 95% CI 2.11 to 110.4; p = 0.007). Conclusion: We observed that 36 mm MoM Pinnacle THAs have an unacceptably high ten-year failure rate, especially if implanted from 2006 onwards or in bilateral MoM hip patients. Our findings regarding implantation year and failure support recent concerns about the device manufacturing process. We recommend all patients undergoing implantation since 2006 and those with bilateral MoM hips undergo regular investigation, regardless of symptoms. Cite this article: Bone Joint J 2017;99-B:592–600.